Extremely Late In-Stent Thrombosis 12 Years After Implantation of a Drug-Eluting Stent - Sleiman, Elsa (Cureus, 2020)
Stent thrombosis is one of the most feared complications of percutaneous coronary intervention. Most commonly it occurs within the first few days after the deployment of the stent. Once the stent is completely endothelialized, this complication becomes extremely rare. Few cases of very late stent thrombosis were reported in the literature with the longest interval being around 11 years after the initial intervention. We report here the case of a 78-year-old male patient who presented with acute onset chest pain found to have acute inferior ST-segment elevation myocardial infarction due to thrombotic occlusion of a prior paclitaxel drug-eluting stent placed 12 years prior. This is, to our knowledge, the first case of stent thrombosis occurring after this long duration since stent implantation.